PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. KUMALA INDONESIA SHIPYARD - EDUARDO SINAGA; NORA PITRI NAINGGOLAN (JURNAL ILMIAH KOHESI, 2020)
Human resource management is a thing that is familiar to a company. Where human resources function as living assets thatplay an important role in the movement of a company. Human resources must be viewed and managed properly from thebeginning which in the future will define the sustainability of the company's life. Once the special position of humanresources as a determinant of the back and forth of a company. Management and leadership of the company has theobligation to design well in this matter, by designing policies that are appropriate for each individual or group that will be builtand formed so that they have the competence to the desired standard. PT Kumala Indonesia Shipyard is a companyengaged in the shipyard industry which is one of the companies that manufactures tankers, barges and cargo ships.Discipline of employees who are still lacking, mastery and skills of employees that have not been enough to affect the resultsof performance for the company and organizational culture that is not going well will certainly affect the pattern of bad habitsthat affect the performance of these employees. The purpose of this study was to determine the effect of partial andsimultaneous variables of work discipline, work experience, and organizational culture on employee performance at PTKumala Indonesia Shipyard. This quantitative study uses a saturated sampling technique for the entire population of 107employees. Data collection was carried out by distributing questionnaires to all respondents using a Likert scale as ameasurement scale and SPSS Version 22 as a data processing application. T Test Results stated that partially thecompensation, motivation, and work environment variables had a positive and significant effect on the performance of theemployees of PT Kumala Indonesia Shipyard. And the F Test results state that simultaneously the compensation, motivation,and work environment variables have a positive and significant effect on the performance of the employees of PT KumalaIndonesia Shipyard.